Application of Red Guava Waste MOL as a Bioactivator in Dairy Goat Feed - Dini Widianingrum; Sri Umyati; Oki Imanudin (Pascasarjana Universitas Mataram, 2025)
Utilization of organic waste as an active ingredient in the manufacture of Local Microorganisms (MOL) is an environmentally friendly innovation that supports efficiency and sustainability in the livestock sector. This study aims to examine the application of MOL based on red guava waste (Psidium guajava L.) as a bioactivator in the formulation of dairy goat rations. Red guava waste MOL was formulated through anaerobic fermentation process and applied as an inoculant in rations based on local ingredients. Observations were made on ration fermentation quality (pH, odor, texture), ration consumption rate, and milk production performance of dairy goats. Results showed that the use of red guava waste MOL increased ration fermentation efficiency, improved palatability, and contributed to increased feed consumption and milk production. In addition, this approach also adds value to fruit waste management and supports sustainable farming practices. The application of MOL from red guava waste proved to be a potential bioactive solution in the development of fermented rations for dairy goats. Conclusion the application of MOL from red guava waste is proven to be effective as a bioactivator in dairy goat rations.